2016
DOI: 10.7439/ijbar.v7i1.2850
|View full text |Cite
|
Sign up to set email alerts
|

Study of serum LDH and GGT levels in carcinoma breast

Abstract: Background: Breast cancer is the second most common cancer in women next only to cervical cancer. Multiple factors are associated with an increased risk of developing breast cancer. For the early detection of carcinoma of breast, a number of biochemical markers have been studied to evaluate the malignancy. Aim: To analyse serum Lactate Dehydrogenase, Gamma Glutamyl Transpeptidase, liver enzymes (SGOT, SGPT, & ALP) and total proteins in diagnosis of carcinoma breast patients and compared with controls. And eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
3
1
0
Order By: Relevance
“…7). Present study findings are in accordance with the study conducted by Basnyat AS et al 9 Guddanti Rajeswari et al 10 , in their study, observed serum LDH is significantly increased in Ca breast patients when compared to controls. In the study of Aditi Agarwal et al .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…7). Present study findings are in accordance with the study conducted by Basnyat AS et al 9 Guddanti Rajeswari et al 10 , in their study, observed serum LDH is significantly increased in Ca breast patients when compared to controls. In the study of Aditi Agarwal et al .…”
Section: Discussionsupporting
confidence: 93%
“…Present study findings are in accordance with the study Basnyat AS et al 9 , Guddanti Rajeswari et al 10 , Jarari et al 16 Choudhari et al 14 andChandrakanth et al 17-----in their study observed serum GGT levels are significantly increased in Ca breast patients when compared to controls and also observed the further significantly increased levels of GGT (P-value <0.0001) in different stages of Ca breast cases compared to control subjects. In contrast, to present study Guddanti Rajeswari et al 10 , in their study, there is a negative correlation (r-value=-0.2105) of serum GGT with ALP levels in the post-menopausal group of breast cancer patients. In the present study, an increase in serum GGT activity is due to the rapid turnover of malignant cells, which release the enzymes into the bloodstream.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our result also supported by some study mentions that level of LDHA is elevated in many malignant tumors and is associated with tumor proliferation and malignant growth, with potential implications for tumor diagnosis and therapy and The high activities of LDH in cancer cells may be due to the process of high cell proliferation, migration, or invasion than normal cells [20]. Our study also study revealed, Gamma glutamyl transpeptidase (GGT) were significantly increased only at grade III (p value 0.022) .These observations were in agreement with the studies of Fentiman, et al [21] and McElroy et al [22]. Other study conducted by Basnyat et al, find that LDH and GGT showed steady and progressive increase in the activities of these enzymes from stage I-IV.…”
Section: Discussionsupporting
confidence: 92%